Formal synthesis of herbarumin III - Gupta, Priti; Kumar, Pradeep (Tetrahedron-Asymmetry, 2007)
An enantioselective synthesis of herbarumin III is described employing Jacobsen's hydrolytic kinetic resolution and Sharpless asymmetric dihydroxylation as the key steps. (c) 2007 Published by Elsevier Ltd.
Keywords: carboxymethyl-cellulase; F. moniliforme; pectate lyase; plant pathogenesis; polygalacturonase; Xylanase

Facile synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone - Upadhyay, Puspesh K.; Prasad, Rajendra; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2009)
A short synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone was achieved from L-serine employing Horner-Emmons olefination as the key step. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Horner-Emmons olefination; L-serine; Pyridone; Z-selectivity

First asymmetric total synthesis of aspinolide A - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
The first total synthesis of aspinolide A has been achieved using ring-closing metathesis as a key step. The stereogenic centers were generated by means of hydrolytic kinetic resolution (HKR) of racemic epoxides. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis

First total synthesis of seimatopolide B - Nookaraju, U.; Harbindu, Anand; Bhise, Ankushkumar D.; Sharma, Brijesh M.; Kumar, Pradeep (RSC Advances, 2012)
The first enantioselective total synthesis of seimatopolide B has been achieved, using ring-closing metathesis and DCC (N,N'-dicyclohexylcarbodiimide) coupling as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides.

Formal synthesis of tetrahydrolipstatin and tetrahydroesterastin - Tripathi, Divya; Kumar, Pradeep (Tetrahedron-Asymmetry, 2012)
A versatile and efficient approach to (3.5,5R)-methyl 3-(benzyloxy)-5-(methoxymethoxy)hexadecanoate, a key chiral building block and a common polyol fragment of the anti-tumor and anti-obesity agents tetrahydrolipstatin 3 and tetrahydroesterastin 4 using both hydrolytic kinetic resolution (HKR) and proline catalyzed sequential alpha-aminoxylation, followed by HWE-olefination reaction is described. (c) 2012 Elsevier Ltd. All rights reserved.

Flexible, polymer-supported synthesis of sphingosine derivatives provides ceramides with enhanced biological activity - El-Dahshan, Adeeb; Al-Gharabli, Samer I.; Radetzki, Silke; Al-Tel, Taleb H.; Kumar, Pradeep; Rademann, Joerg (Bioorganic & Medicinal Chemistry, 2014)
A polymer-supported route for the synthesis of sphingosine derivatives is presented based on the C-acylation of polymeric phosphoranylidene acetates with an Fmoc-protected amino acid. The approach enables the flexible variation of the sphingosine tail through a deprotection-decarboxylation sequence followed by E-selective Wittig olefination cleavage. D-Erythro-sphingosine analogs have been synthesized by diastereoselective reduction of the keto group employing LiAlH(O-tBu)(3) as reducing agent. The effect of ceramides and keto-ceramides on the proliferation of three cancer cell lines HEP G-2, PC-12 and HL-60 was investigated and a ceramide containing an aromatic sphingosine tail was identified as being most active. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Ceramide; Lipid rafts; Lipids; Sphingosine

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis